Hounsfield Units (HU) as a Predictor of Stone Clearance after Percutaneous Nephrolithotomy (PCNL) - Muhammad Akhtar, Muhammad Umar Khan, Zeeshan Zafar, Sarfraz Hassan, Muhammad Hamza Khan Lodhi, Hafiz Muhammad Usman, Mm Khan (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To compare the outcomes of percutaneous nephrolithotomy (PCNL) in patients with renal stones with high (≥700) versus low (<700) HU. Patients and Methods: A total of 200 patients having age 18 to 60 years, with diagnosis of unilateral renal stone disease, having stone size 2 to 4 cm in diameter on non-contrast computed tomography (NCCT) of Urology Unit of Ibn e Sina Hospital and Research Institute Multan were included. The study duration was May-2021 to July-2021. NCCT was done pre-operatively in every patient to measure Hounsfield units (HU). Post-procedural X-ray KUB was done 2 weeks after the surgical procedure to determine the stone clearance in every patient. Results: Mean age was 45.79±11.17 Years. Mean duration of disease of patients included in this study was 8.78±8.59 months. Mean stone size in patients included in this study was 3.11±0.61 cm. On comparison of stone clearance rate between the patients having high-HU versus low-HU, stone clearance was found in 61 (72.6%) patients having low HU value and in 105 (90.5%) patients having high HU value (p-value 0.001). Conclusion: HU-value ≥700 is a significant predictor of success rate of percutaneous nephrolithotomy (PCNL) in patients having renal stone disease. Keywords: Renal Stone Disease, Percutaneous nephrolithotomy, Hounsfield units (HU).